Regeneración posincendio de plantas leñosas en plantaciones de Pinus radiata D. Don, zona costera, Región del Maule, Chile central - GÓMEZ, PERSY; HAHN, STEFFEN (Gayana Botánica, 2017)
We evaluated the regeneration of woody species in Pinus radiata plantations. The objective was to determine the recovery of vegetation from fires. The results indicated that 93% of the species are resprouters already present in the site before the fires. The most representattive familia were Anacardiaceae, Fabaceae and Rosaceae. Considering frecuency, coverage and relative density, the most important species are: Lithrea caustica, Schinus polygamus and Kageneckia oblonga. Lithrea caustica was the species that generated a great amount of sprouts some of them reaching to 95 cm. There was no regeneration of P. radiata but it may be only a matter of time.